O17 Treatment target in newly diagnosed SLE patients: low disease activity and remission are independently associated with lower accrual of early damage. (23rd March 2020) - Piga, Matteo; Floris, Alberto; Perra, Daniela; Chessa, Elisabetta; Congia, Mattia; Mathieu, Alessandro; Cauli, Alberto
Abstract : Background/Purpose: To compare the independent effect of achievement and maintenance of lupus low disease activity state (LLDAS) and clinical remission (CR) in preventing early damage accrual in the early stage of systemic lupus erythematosus (SLE) management. Methods: In a monocentric inception cohort of 116 newly diagnosed SLE patients, LLDAS and CR achievement at 6 months (T1) after treatment initiation and their maintenance over the next 12 (T2) months were assessed. Early damage was assessed (T2) using the SLICC/damage index. Uni- and multivariate analysis were performed to evaluate the association of LLDAS and CR with early damage. Results: LLDAS achievement was significantly more frequent than CR both at T1 (42.2% vs. 21.6%, p<0.001) and T2 (46.6% vs. 31.9%, p=0.022), with an increasing trend in the overlap rate observed over follow-up (from 51.0% at T1 to 68.5% at T2). Higher SLEDAI score (OR: 1.33, 95%CI 1.04–1.71, p 0.022) at baseline, but not higher prednisone dose, was associated with failure to achieve CR at T1. The overlap between persistent LLDAS and persistent CR between T1 and T2 was observed in 41.7% of cases. On multivariate analysis, the achievement of CR (OR 0.1, 95%CI 0.01–0.59, p=0.015) and LLDAS without CR (OR 0.2; 95%CI 0.06–0.99, p=0.049) at T1, as well as younger age at onset (OR 0.95, 95%CI 0.91–0.98, p=0.004), were negatively associated with early damage. Patients who achieved LLDAS at T1 and steadily persisted in this condition until T2 developed significantly less damage compared to those who failed to maintain it during the T1-T2 interval (p=0.003), those who achieved it later than T1 (p<0.001) or those who had never been in this condition (p<0.001). Conclusions: Although CR is recommended as the primary treatment target in SLE, LLDAS may represent a valid alternative in the early stage of SLE management. LLDAS and CR maintenance should be targeted to prevent damage.